Spirituality, Mental Health and Quality of Life Pathways in Indian Psychology - Pant, Naveen (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book is about spiritual intelligence and its effects on mental health and quality of life. As mental health and related problems are increasing rapidly and have become a matter of great concern, there has not been a unanimous and empirical approach to assess and cure it, due to its divergence or other causes. This book is based on the most developed construct: spiritual intelligence and its effects on mental health and quality of life. Spirituality and its other constructs are one of the most interesting topics nowadays in the area of positive/indigenous/transpersonal psychology and among social/behavioral scientists. This book provides content on spirituality, spiritual intelligence, mental health, and quality of life. The book also attempts to review related literature (whether review or empirical), to have a look at past and current scenarios on spirituality and mental health and quality of life research. Through an exploration of Indian indigenous psychology, this book provides a look at mental health and the mind from an Indian psychological perspective and examines Indian psychology, taking into consideration modern psychological concepts.
1. Introduction;- 2. Spirituality, Mental Health and Quality of Life: An Introduction -- 3. The Relationship of Spirituality with Mental Health and Quality of Life: A Review -- 4. The Role of Spirituality in Predicting Mental Health and Quality of Life Among Early Adults -- 5. Indian Psychology of Mind and Mental Health.
Keywords: Psychology; Mental health; Quality of life; Spirituality; Positive psychology; Religion; Behavioral Sciences and Psychology; Mental Health; Quality of Life Research; Spirituality; Positive Psychology; Religion